Increasing Job Satisfaction Through Transformational Leadership: Mediated by Organizational Culture and Work Motivation - I Komang Suryadnya Diputra; Putu Ari Pertiwi Sanjiwani; Bagus Nyoman Kusuma Putra (Media Ekonomi dan Manajemen, 2024)
The tourism industry in Bali is currently experiencing improvement after experiencing hibernation during the pandemic. This situation will certainly have an impact on all supporting businesses, including hotels in general and employees in particular. This research aims to investigate the relationship between transformational leadership and organizational culture, work motivation, and job satisfaction. Survey data was collected from 264 four-star hotel employees in Bali. Then the data was analyzed using Smart PLS 3.2.9. The findings of this research show that transformational leadership has no effect on job satisfaction, but has a significant effect on organizational culture and work motivation. Furthermore, organizational culture and work motivation act as mediators of the relationship between transformational leadership and job satisfaction. Thus, organizational culture and work motivation play an important role in maintaining and increasing job satisfaction. In addition to showing direct influence, they also act as mediators.